In vitro growth characterization and biocontrol potential of naturally occurring nematophagous fungi recovered from root-knot nematode infested vegetable fields in Benin - AFFOKPON, ANTOINE; Coyne, Danny L.; De Proft, Maurice; Coosemans, Jozef (My University, 2015)
Naturally occurring fungal antagonists of root-knot nematodes (Meloidogyne spp., RKNs) were collected from 88 root and corresponding rhizosphere soil samples from 50 intensively cultivated fields used for peri-urban vegetable production in Benin, West Africa. Five species of Trichoderma viz.: T. asperellum, T. harzianum, T. brevicompactum, T. hamatum and T. erinaceum and four isolates of Pochonia chlamydosporia were isolated from RKN egg masses on root systems of crops and/or infested soil. During temperature-tolerance assessment studies, most isolates had maximum growth rates in Petri dishes at 28 C. Chlamydospore production by P. chlamydosporia was high in 2:1 v/v sand-milled corn medium. In pots, P. chlamydosporia isolates showed high ability to colonize and persist in tomato rhizosphere over 10 weeks. Pre-planting application with some P. chlamydosporia isolates led to up to 50% infected eggs and 25% reduction of RKN multiplication and root galling damage. This study provides valuable information for the mass rearing of the respective fungal inoculum and the first information on the potential of West African P. chlamydosporia isolates for use against RKN in vegetable production systems
Keywords: antagonistic bioagents; biodiversity; biological control; Meloidogyne spp.; peri-urban vegetable systems; West; Africa